PROSES PRODUKSI DAN PENANGAN PENYIMPANAN DINGIN IKAN ANGOLI WHOLE GILLED (WG) (Pristipomoides multidens) - Azkal Azkiya’, Ahmad; Izah, Nikmatul; Ainiyah, Roisatul; Putri Pamungkas, Pinctada (Lempuk: Jurnal Ilmu Kelautan dan Perikanan, 2025)
The processing of Whole Gilled (WG) angoli fish (Pristipomoides multidens) is an effort to maintain the quality and freshness of the product before being exported, particularly to Singapore. This study was conducted during an internship at PT. Inti Luhur Fuja Abadi (ILUFA) and aimed to describe the flow process of receiving, cleaning, gutting, freezing, packaging, and stuffing of WG angoli fish. Methods used include direct observation, interviews, and documentation. The results show that the company implements strict quality control including temperature regulation, metal detection, and FIFO system in cold storage. This ensures product safety, hygiene, and traceability. The processing sequence starts from the reception of raw material to the final export preparation stage. The findings provide a good reference for handling high-quality fishery products in industrial settings.